1996
DOI: 10.1017/s0022112096007446
|View full text |Cite
|
Sign up to set email alerts
|

Shear-free turbulence near a flat free surface

Abstract: In this study the evolution of initially homogeneous and isotropic turbulence in the presence of a free surface was investigated. The Navier–Stokes equations were solved via direct pseudo-spectral simulation with a resolution of 963. The Reynolds number based on the volume-averaged turbulence kinetic energy and dissipation rate was 147. Periodic boundary conditions were used in two dimensions, and the top and bottom sides of the domain were flat and shear-free. A random, divergence-free velocity field with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
88
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 20 publications
17
88
1
1
Order By: Relevance
“…It has been shown that the flow at the free surface is highly anisotropic. 18 Also, as mentioned in the Introduction, Walker et al 8 found that the vertical gradient of the horizontal vorticity vanished only in a very thin layer near the free surface, requiring a fine grid to resolve the mean profile in that region. Shen and Yue 18 show that the energy backscatter ͑transfer from subgrid scales to larger scales͒ is maximal at the free surface.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…It has been shown that the flow at the free surface is highly anisotropic. 18 Also, as mentioned in the Introduction, Walker et al 8 found that the vertical gradient of the horizontal vorticity vanished only in a very thin layer near the free surface, requiring a fine grid to resolve the mean profile in that region. Shen and Yue 18 show that the energy backscatter ͑transfer from subgrid scales to larger scales͒ is maximal at the free surface.…”
Section: Methodsmentioning
confidence: 93%
“…I, previous studies 8,9 have shown that turbulence at a free surface without the presence of stratification cannot be well represented by twodimensional dynamics. It is generally thought that stratification tends to make turbulence more two-dimensional, so it might be anticipated that, with sufficient stratification, the dynamics at the free surface might be approximated by a two-dimensional model.…”
Section: ͑54͒mentioning
confidence: 99%
See 1 more Smart Citation
“…A difference between the results of the present work and those of Hsu et al (2000) is that the recovery of u u occurs across almost all the surface, except at the lower-wall bisector where ∂ u /∂y is equal to zero and ∂ u /∂z values are almost constant in the region 0.8 < z/D < 1. Previous studies of Perot & Moin (1995) and Walker et al (1996) revealed significant differences between shear-free boundary layers near solid walls and free surfaces, such as the higher tangential Reynolds stress and lower dissipation near a free surface. Walker et al (1996) attribute the apparent increase of turbulence kinetic energy near a rigidlid boundary to the reduced dissipation of the tangential velocity fluctuations.…”
Section: Open Duct: Reynolds Stressesmentioning
confidence: 96%
“…velocity-fluctuation profiles exhibit trends similar to open channel flows. Indeed, u rms dominates, and near the free surface, turbulence moves towards a quasi-twodimensional state (see Walker et al 1996). From a mathematical point of view, this behaviour at the centre of the duct is obvious since the Reynolds stresses depend on the shear components, most of which are zero at the centre of the duct since symmetry and fully developed conditions are assumed.…”
Section: Open Duct: Reynolds Stressesmentioning
confidence: 99%